Lego Serious Play: a three-dimensional approach to learning development - James, Alison Rosemary (Journal of Learning Development in Higher Education, 2013)
This paper discusses work underway to explore the use of Lego Serious PlayÃÂ (LSP) as an unconventional means of developing student learning. Designed originally as a thinking tool within the corporate sector, the techniques and applications of LSP are not those conventionally used in developing academic capacities within students. However, experiences with LSP at the London College of Fashion and that of users in other settings offer evidence of its value in aligning with other approaches to learning to provide a non-hierarchical and student-centred lens through which to consider personal growth and subject understanding.ÃÂ This paper suggests that LSP has an important role to play in supporting multisensory approaches to reflecting on learning, either in tandem with, or instead of writing. While the use of LSP discussed here focuses on its implementation on creative arts courses, it is a highly transferable methodology which can be applied across the spectrum of disciplines and for multiple purposes.